Possible Association of APOE Genotype with Working Memory in Young Adults. - Lindsey I Sinclair; Katherine S Button; Marcus R Munafò; Ian N M Day; Glyn Lewis (PLoS ONE)
Background Possession of the ε4 allele of the Apolipoprotein E (APOE) gene is associated with an increased risk of Alzheimer's disease. Early adult life effects of ε4 are less well understood. Working memory has been relatively little studied (compared to episodic memory) in relation to APOE genotype despite its importance in cognitive functioning. Our hypothesis was that ε4 would lead to an impairment in working memory in young adults. Methods We studied working memory using a computerised n-back task in the Avon Longitudinal Study of Parents and Children (ALSPAC) at age 18. Data was available for 1049-1927 participants and for the 2- and 3-back versions of the task. Using multiple and multi-level regression controlling for important confounders we examined the association between APOE genotype on accuracy and reaction times. Results There was no evidence of a genotype effect on accuracy when the two difficulty levels were examined separately. There was some evidence to support a deleterious effect of the ε4 allele on n-back accuracy in the multi-level regression. There was weak evidence that the ε22 group were less accurate but the numbers were very low in this group. The ε34 group had faster reaction times than the reference ε33 group in all adjusted analyses but the ε44 group were only faster in the 3-back condition in multi-level analyses. Conclusions There was no evidence of benefit in ε4 carriers, but there was some evidence of a detrimental effect on working memory in this large study.